Synthesis of N-(hydroxymethylene)thioamides by N-hydroxymethylation of 2-cyanothioacrylamides - Arina G. Levchenko; Polina G. Dahno; Victor V. Dotsenko (Chemistry Proceedings, 2021)
The condensation products of cyanothioacetamide with aldehydes—(E)-arylmethylenecyanothioacetamides—have proven to be readily available and multifunctional starting reagents in the chemistry of S,N-containing compounds. We decided to study the interaction of formaldehyde with thioamides as a possible way to obtain N-(hydroxymethylene)thioamides, which are promising thioamidoalkylating agents and new ligands for complexation. It was found that the reaction of thioamides and formaldehyde proceeds easily when the reagents are heated in the absence of catalysts in an aqueous-alcohol medium, and leads, with good yields, to the expected N-(hydroxymethylene)thioamides. The structure of N-(hydroxymethylene)thioamides 2 was confirmed by IR and NMR spectroscopy data.